ON THE UNIFORM APPROXIMATION OF AN INNER FUNCTION - Pandeski, Nikola (Matematichki Bilten, 2002)
The inner function \(\exp\left(-\frac{1+z}{1-z}\right)\) we approximate uniformly in the unit disk by interpolating Blaschke products.